Integrating Andragogy Principles in Employee Training: Literature Study - Anzar Agustian; Hiryanto Hiryanto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to analyze and synthesize the results of research on the integration of andragogy principles in employee training and identify best practices for its application in human resource development. The research uses the literature study method (library research) with a descriptive-qualitative literature review approach. The research data is in the form of secondary data sourced from 10 national and international journal articles published in 2017–2025 which were obtained through Google Scholar, Scopus, SINTA, Garuda, and ResearchGate. Data collection is carried out through documentation studies, while data analysis uses content analysis which includes data reduction, theme grouping, data presentation, and conclusion drawn. The results showed that the application of andragogy principles, such as self-directed learning, relevance of the material to work needs, utilization of participant experiences, problem-based learning, and intrinsic motivation, contributed to increased participant engagement, skill retention, learning satisfaction, and training effectiveness. In addition, the integration of digital technologies, gamification, and artificial intelligence expands the implementation of andragogy in modern training that is more adaptive. In practical terms, these findings provide a basis for organizations to design participatory, contextual, and flexible training. Theoretically, this study strengthens the relevance of andragogy as an adult learning approach in an organizational context. Further research is suggested to test the effectiveness of an andragoggy-based training model through empirical studies on various industrial sectors.